Seagrass community structure in the waters of Terkulai Island, Tanjungpinang City - Yani, Fatma Chairda; Susiana, Susiana; Nugraha, Aditya Hikmat; Rochmady, Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
Seagrass ecosystem is a coastal ecosystem where seagrass grows as the dominant vegetation and can live permanently below sea level. Of course, the existence of human activities that do not care about the coastal environment has an impact on changes in seagrass communities in supporting coastal ecosystems. This study aims to determine the structure of the seagrass community in Terkulai Island Waters, Tanjungpinang City, this research was conducted in May 2023. Determination of the sampling point was carried out using the purposive sampling method with 4 stations that have seagrass distribution. Observation of seagrass was carried out using the modified line transect method where the line transect was placed at the starting point where seagrass was found until the end point was not found, the transect placement was chosen based on the longest area of the seagrass stretch and as a benchmark the transect placement was squared 50 x 50 cm then each line transect length was divided by 10% to get the squared distance between transects. The results of the study found 3 types of seagrass in the waters of Terkulai Island namely Enhalus acoroides, Thalassia hemprichii, Halophila ovalis. Seagrass Thalassia hemprichiii has the highest density when compared to other seagrass species with density values ranging from 764 to 1928 shoots/m2. If categorized, the value of seagrass cover at each station is included in the medium category. For seagrass biomass the Enhalus acoroides type is larger when compared to other seagrass species. The results of PCA (Principal Component Analysis) showed that seagrass cover was closely related to the environmental parameter characteristics of depth, brightness, salinity.